PKM PENGEMBANGAN DAN APLIKASI TRICHODERNA Sp PADA TANAMAN BAWANG MERAH - Surnaherman, Surnaherman; Lubis, Wildani; MD, Masyhura (Universitas Muhammadiyah Tapanuli Selatan, 2022)
Root rot or stem and fusarium wilt are the diseases that come often to onion plant that may impair growth and also reduce onion production. The holocaust of root rot or stem and fusarium wilt is often to take of by chemical pesticides. This way can destroy the earth and circuit for the reduce onion production. To reduce chemical pesticides use, treat the earth, and increase onion production, the solution is organic pesticides used by trichoderma sp. Trichoderma sp is vegetable pesticides as antagonistic bacteria which have many benefit to increase the quality of onion production for enviromentally friendly by control OPT. PKM team do development training of trichoderma sp by point trichoderma sp usely. The Partner or farmers in Medan Marelan district i.e Kelompok Tani Karya Maju and Kelompok Tani Karunia. The development of high quality trichoderma sp and most economic value may spread in product marketing hopefully.